Imperial ideology and provincial loyalty in the Roman Empire - Ando, Clifford, 1969- (Classics and contemporary thought ;, 2000)
This text examines why and how the Roman empire lasted so long. In studying the bureaucracy behind it, the author argues that the longevity of the empire rested not on military power but on a gradually realized consensus that Roman rule was justified.